Serum Levels of Soluble IL-2R, CD4 and CD8 in Chronic Active HCV Positive Hepatitis - C. Caruso; G. Candore; D. Cigna; S. Tripi; G. Di Gaetano; G. Migneco; G. Montalto; I. Ruggieri; A. Notarbartolo (Hindawi Limited, 1994)
The aim of the present study was to compare serum levels of soluble forms of interleukin-2 receptor, CD4 and CD8, released by lymphocytes during activation ofthe immune system, in patients with histologically verified chronic active hepatitis associated to hepatitis C virus infection, with those in healthy subjects. Significantly higher levels of soluble IL-2R and soluble CD8 were found in patients with chronic active hepatitis compared with controls. In contrast no difference was found for soluble CD4 values in the two groups. No correlations were found for both sIL-2R and sCD8 and these two molecules with other parameters of liver function. These results indicate that in these patients there is a general activation of the immune system, but the lack of correlation with parameters of liver function strengthens the suggestion that this activation does not play a role in the pathogenesis of chronic type C hepatitis.